The Eco-Immunological Relevance of the Anti-Oxidant Response in Invasive Molluscs - Davide Malagoli; Nicola Franchi; Sandro Sacchi (MDPI AG, 2023)
Reactive oxygen species (ROS) are volatile and short-lived molecules playing important roles in several physiological functions, including immunity and physiological adaptation to unsuitable environmental conditions. In an eco-immunological view, the energetic costs associated with an advantageous metabolic apparatus able to cope with wide changes in environmental parameters, e.g., temperature range, water salinity or drought, could be further balanced by the advantages that this apparatus may also represent in other situations, e.g., during the immune response. This review provides an overview of molluscs included in the IUCN list of the worst invasive species, highlighting how their relevant capacity to manage ROS production during physiologically challenging situations can also be advantageously employed during the immune response. Current evidence suggests that a relevant capacity to buffer ROS action and their damaging consequences is advantageous in the face of both environmental and immunological challenges, and this may represent a trait for potential invasiveness. This should be considered in order to obtain or update information when investigating the potential of the invasiveness of emerging alien species, and also in view of ongoing climate changes.